Pengaruh Pembelajaran IPA Terpadu Menggunakan Model Pembelajaran Berbasis Proyek Sebagai Solusi Pembelajaran Di Era Pandemi - elsa dwi agung kurniafin; Indica Yona Okyranida (UNIVERSITAS INDRAPRASTA PGRI, 2021)
In Madrasah Tsanawiyah negeri 9 Blitar in the academic year 2020/2021 even semester applies online / online learning. In integrated IPA learning, the project-based spelling model was chosen as a solution in online learning because it was in accordance with the learning objectives in school. Project learning for grade VIII students uses video projects about vibrations and waves. Vibrational and wave material is so close to everyday life that with the application of the project learning model aims to improve student achievement. The population of class VIII students in MTS 9 Blitar is 191 students, with 31 student subjects. The research method used is quantitative descriptive by comparing the average results of value before and after learning. The result of the study is that there is an influence of integrated IPA learning using project-based learning models on students' cognitive learning outcomes. Project assignments also have a positive influence on students' responses in the field of independence and cooperation.